Entrepreneurial Intentions: The Effect of Proactive Personality in Perspective of Planned Behavior Theory as an integrated approach in the Indonesian Context - Elissa Dwi Lestari; Hillary Suris Kusuma; Wanthing Fortuna Marlim (ADI Publisher, 2021)
Entrepreneurship in Indonesia is still relatively low and lagging behind other ASEAN countries because the number of entrepreneurs in Indonesia has only reached 3.47% of the total population. College students have become one of the vital sources of supply for entrepreneurs in Indonesia. Therefore, to increase the number of entrepreneurs, the Indonesian government encourages higher education to produce graduates looking for work and creating jobs. Even though the government and universities have tried to increase the number of entrepreneurial students, the number of students who choose entrepreneurship as a professional career choice is still low. This research was conducted to see how students' entrepreneurial intention (EI) in Indonesia as a forecaster of entrepreneurial behaviour. The research analyses the effect of proactive personality traits and the theory of planned behaviour (TPB) as an integrated model, with the TPB dimension as a mediator. The research was conducted by using judgmental sampling of 387 students in Indonesia. Data collection was carried out using an e-survey, and data were analyzed using structural equation modelling with Partial Least Square (PLS). Research result shows that proactive personality and TPB are predictors of students' entrepreneurial intentions. This study also shows that TPB mediates the relationship between proactive personality towards Student' entrepreneurial intention. The results of this study are expected to contribute to the EI study of students in Indonesia. Scientifically, this research is also expected to enrich the EI literature by integrating proactive personality as an antecedent of TPB and EI.